BDA-410 Treatment Reduces Body Weight and Fat Content by Enhancing Lipolysis in Sedentary Senescent Mice - Pereyra, Andrea Soledad (2017)
Loss of muscle mass and force with age leads to fall risk, mobility impairment, and reduced quality of life. This article shows that BDA-410, a calpain inhibitor, induced loss of body weight and fat but not lean mass or skeletal muscle proteins in a cohort of sedentary 23-month-old mice. Food and water intake and locomotor activity were not modified, whereas BDA-410 treatment decreased intramyocellular lipid and perigonadal fat, increased serum nonesterified fatty acids, and upregulated the genes mediating lipolysis and oxidation, lean phenotype, muscle contraction, muscle transcription regulation, and oxidative stress response. This finding is consistent with our recent report that lipid accumulation in skeletal myofibers is significantly correlated with slower fiber-contraction kinetics and diminished power in obese older adult mice. A proteomic analysis and immunoblot showed downregulation of the phosphatase PPP1R12B, which increases phosphorylated myosin half-life and modulates the calcium sensitivity of the contractile apparatus. This study demonstrates that BDA-410 exerts a beneficial effect on skeletal muscle contractility through new, alternative mechanisms, including enhanced lipolysis, upregulation of "lean phenotype-related genes," downregulation of the PP1R12B phosphatase, and enhanced excitation- contraction coupling. This single compound holds promise for treating age-dependent decline in muscle composition and strength.